Research on Optimization of Post-competition Training Methods for Competitive Sports Athletes - Chenyang Xia; Xiaoming Lei, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
Athletes enter a competitive sport for various reasons and go on to compete for years without any significant modifications that may affect the success of their sporting career. However, there is a cost to this approach of no changes in training strategy. The purpose of this study was to identify successful post-competition training methods by studying both international and Olympic athletes compete in multiple endurance sports during the World Championships event. Results showed several factors including personal characteristics, coaching knowledge, skill level, competition phase and season can have a significant impact on the success rates of athletes following competition performance. In this study, five factors were employed, and the results were published. The information was gathered using a questionnaire from 50 kids who participated in sports. However, the gathered data was subjected to SEM PLS 3 analysis. The findings revealed a favorable relationship between the five variables that were studied.